2012
DOI: 10.1186/1479-5868-9-1
|View full text |Cite
|
Sign up to set email alerts
|

Health-related knowledge and preferences in low socio-economic kindergarteners

Abstract: ObjectiveThe aim of the present study was to determine physical activity (PA) and nutrition knowledge and preferences in low socio-economic status kindergarten children.MethodsFollowing height and weight measurement, 795 low socio-economic status kindergarten children (age 3.8-6.8 y.o) completed a photo-pair knowledge and preferences food and exercise questionnaire.ResultsNo difference was found between nutrition and PA knowledge scores (52.3 ± 0.9 versus 52.6 ± 0.8%, respectively). There was no difference bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
194
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(215 citation statements)
references
References 17 publications
14
194
7
Order By: Relevance
“…39 Another study found that neighborhood walkability had a stronger influence on walking for transport among women than among men, which directly contrasts with the findings presented in this study. 40 Among Asian Americans in particular, one study found that neighborhood factors did not explain low rates of walking, which also contrasts with the findings for South Asian American men presented in this study. 23 …”
Section: Discussioncontrasting
confidence: 99%
“…39 Another study found that neighborhood walkability had a stronger influence on walking for transport among women than among men, which directly contrasts with the findings presented in this study. 40 Among Asian Americans in particular, one study found that neighborhood factors did not explain low rates of walking, which also contrasts with the findings for South Asian American men presented in this study. 23 …”
Section: Discussioncontrasting
confidence: 99%
“…Blacks, Hispanics, and those with few socioeconomic resources tend to be more sedentary than whites or those with more socioeconomic resources [46, 51]. Indeed, children in low income families have greater access to televisions, DVD players, and video games in their bedrooms than children in higher income families [52]. …”
Section: Mechanisms and Potential Interventionsmentioning
confidence: 99%
“…For instance, studies have shown that physical activity and fitness are separable at the level of individual differences (Jacobs et al, 1993; Laye et al, 2015; Williams, 2001), either because it is feasible that the same individual can achieve daily moderate-to-vigorous exercise while being sedentary the rest of the day (Craft et al, 2012; Pate et al, 2008), or because there are determinants of cardiorespiratory fitness that account for variance beyond habitual physical activity such as genetics, which may account for about half of the variance in individual differences in fitness (Bouchard et al, 1999; Bouchard et al, 2011). In addition, more nuanced approaches for objectively measuring physical activity are now available (Chen et al, 2012; Rowlands et al, 2015), and these provide an opportunity to more objectively test what features of daily physical activity (Copeland and Esliger, 2009; Tudor-Locke et al, 2013) are associated with brain health in aging populations (Makizako et al, 2014; Varma et al, 2014).…”
Section: Introductionmentioning
confidence: 99%